PELAKSANAAN PERMUKAAN PERKERASAN BLOK BETON TERKUNCI DI ATAS LAPIS PENDUKUNG FLEKSIBEL - Lawalata, Greece Maria; Agah, Heddy R. (Jurnal HPJI, 2018)
AbstractÂ The provision of sidewalks of locked concrete block is often found in various cities and districts, and many of these enclosures have broken sidewalks, such as sidewalks, sagals, uneven concrete blocks, and can not drain water. In order for the quality of the sidewalk to last a long time need to be studied methods of implementation more precise. This paper discusses some implementation standards, namely the General Specification of Bina Marga 2010 as the basis for technical implementation of pedestrian paths, road-theory and practice projects, paving block specifications by Cisangkan, field guide to hardscape by Hopper. The study also conducted on several other standards. Support data obtained from direct observation in the field at several locations. The results of the study indicate that the implementation of concrete block work in some cities of Bandung has not been optimal. General Specification of Bina Marga 2010 needs to be added related to the implementation of more detailed concrete blocks. Implementation, among others, by preparing sublayer material (subgrade, subbase, base) is good. The density of sand density testing should be maintained to achieve a thick layer of sand. Installation of concrete blocks is immediately done on the sand layer with the difference in the distance of the sand layer and the preparation of concrete blocks approximately one meter to keep the sand thickness. Installation of concrete blocks must be followed by solidification using a specific tool and sand filling between concrete blocks.Â Keywords: locked concrete block, sidewalk, sand, pedestrianÂ Â AbstrakÂ Penyediaan trotoar permukaan blok beton terkunci sering dijumpai di berbagai kota dan kabupaten. Tetapi banyak dijumpai trotoar permukaan blok beton terkunci ini rusak. Agar kualitas trotoar ini bertahan lama, perlu dikaji metode pelaksanaan yang lebih tepat. Makalah ini membahas beberapa standar pelaksanaan, yaitu Spesifikasi Umum Bina Marga 2010 sebagai dasar pelaksanaan teknis jalur pejalan kaki, proyek jalanâteori dan praktek, spesifikasi paving blok oleh Cisangkan, field guide to hardscape oleh Hopper. Kajian juga dilakukan terhadap beberapa standar lain. Data pendukung didapat dari pengamatan langsung di lapangan pada beberapa lokasi. Hasil kajian menunjukkan bahwa pelaksanaan pekerjaan blok beton di beberapa kota Bandung belum optimal. Spesifikasi Umum Bina Marga 2010 perlu ditambahkan terkait pelaksanaan blok beton yang lebih rinci. Pelaksanaan tersebut antara lain dengan mempersiapkan material lapis pendukung (subgrade, subbase, base) yang baik. Upaya uji coba pemadatan lapisan pasir perlu dipertahankan untuk mencapai tebal padat lapisan pasir. Pemasangan blok beton secepatnya dilakukan di atas lapisan pasir dengan perbedaan jarak lapisan pasir dan penyusunan blok beton kurang lebih satu meter untuk menjaga ketebalan pasir. Pemasangan blok beton harus diikuti dengan pemadatan menggunakan alat tertentu dan pengisian pasir antara blok beton.Â Kata-kata kunci: blok beton terkunci, trotoar, pasir, pejalan kaki